OC-051 Practicalities of setting up a new procedure room in endoscopy. (22nd June 2015) - Taggart, N; Batterton, J; McGuinness, D; Flavell, L; Haslam, N; Sarkar, S
Abstract : Introduction: A fifth endoscopy room was set up at the Royal Liverpool Hospital (RLH) October 2014; this was necessary to guarantee an increased capacity in order to meet current and predicted service needs. This was to accommodate the increase in activity from upper and lower GI investigation including the Be Clear on Cancer campaign, the bowel cancer screening programme (BCSP) and rise in complex endoscopy. Method: Aim : This is a reflective look at a room set up. What was achieved by its set up and what lessons have been learned through the process. Prior to implementation : 4 rooms were undertaking 17, 500 procedures per year with 25% inpatients 75% day-case activity. Waiting times were urgent 2 wks, routine 6 weeks, and surveillance 6 weeks. Due to the rise in referrals extra lists were being planned at weekends in order to maintain current targets. The cost of the waiting lists for the year was £400, 000.00 running 200 lists in 2014. Staff often worked during the week and the weekend which impacted negatively on work life balance. Resource planning 10 extra sessions were created. A sound business case was needed to support the £375, 000.00 investment. A stack system was purchased. Extra scopes purchased to support increased lists. Consideration made regarding purchase of extra stock and consumables. Further storage areas needed to be found to house equipment. Close links developed with estates teams and architects. Workforce planning and implementation. A collaborative approach between Trust, Consultants, Nurse Managers, Administration and Human Resources and nursing unions was necessary to ensure full staff engagement as job plans and contracts had to be altered. The increased workload required a long term investment of; 1 X WTE Nurse Endoscopist (for training and 6 lists), 5X WTE Nurses/6 WTE HCAs, 1 X WTE Admin. Consultant endoscopists opt in to extra sessions. Operational issues: Space in recovery is premium staff now discharge all un-sedated patients directly from procedure room. New roles established, band four staff to assist in discharging. Assessment of environmental limitations, considerations need to be made on single sex pathways. Results: All routine and 2ww targets have been maintained. No WLI sessions to date. Complex therapy lists have increased by two/three sessions per week. Able to facilitate an extra two lists for colonoscopy per week. Work-force flexibility and a steady communication with admin manager has meant 95% utilisation for all sessions. Conclusion: An extra endoscopy room improves capacity and reduces waiting times but needs workforce planning and significant capital investment. Environmental constraints will need careful consideration. Creating a new room requires planning, leadership, workforce flexibility and a dedicated team. Disclosure of interest: None Declared.